1991
DOI: 10.1128/mcb.11.12.6296
|View full text |Cite
|
Sign up to set email alerts
|

Natural and synthetic DNA elements with the CArG motif differ in expression and protein-binding properties.

Abstract: DNA elements with the CC(A/T)6GG, or CArG, motif occur in promoters that are under different regulatory controls. CArG elements from the skeletal actin, c-fos, and myogenin genes were tested for their abilities to confer tissue-specific expression on reporter genes when the individual elements were situated immediately upstream from a TATA element. The c-fos CArG element, also referred to as the serum response element (SRE), conferred basal, constitutive expression on the test promoter. The CArG motif from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 58 publications
(76 reference statements)
2
28
0
1
Order By: Relevance
“…Based on observations that substitution of the c-fos SRE consensus CArG for the SM α-actin 5′ CArGs had no detectable effect on SMC specificity in vivo, we questioned whether SRF binding affinity was altered as significantly as would be predicted based on previous EMSA analyses of a wide range of SRE consensus CArG substitution mutants (16)(17)(18)(19). EMSAs previously done in our lab showed that the SRE consensus CArG, in the context of the c-fos promoter, bound SRF with greater activity than either CArG-A or CArG-B in the context of the SM α-actin promoter (7).…”
Section: Resultsmentioning
confidence: 99%
“…Based on observations that substitution of the c-fos SRE consensus CArG for the SM α-actin 5′ CArGs had no detectable effect on SMC specificity in vivo, we questioned whether SRF binding affinity was altered as significantly as would be predicted based on previous EMSA analyses of a wide range of SRE consensus CArG substitution mutants (16)(17)(18)(19). EMSAs previously done in our lab showed that the SRE consensus CArG, in the context of the c-fos promoter, bound SRF with greater activity than either CArG-A or CArG-B in the context of the SM α-actin promoter (7).…”
Section: Resultsmentioning
confidence: 99%
“…Mutation of the MCK enhancer CArG element, a potential binding site for serum response factor (36,56,68), had no dramatic effect on transgene expression in either adult cardiac or skeletal muscle. Although it is possible that a conserved CArG consensus sequence at nt Ϫ177 compensated for the mutation of the enhancer CArG element, this compensation clearly fails to occur in cultured muscle cells, in which the same mutation in the enhancer CArG site produced a loss of transcriptional activity in both cardiomyocytes and skeletal myocytes (2).…”
Section: Discussionmentioning
confidence: 99%
“…This CArG sequence is completely conserved between the rabbit, mouse, rat, and human MCK genes (16,18,37,45), but the functional significance of this MCK sequence had not been documented prior to this study. The CArG motif forms the core of regulatory elements in a number of muscle-specific as well as immediate-early genes (29,38), and the proximal CArG motif of the skeletal actin gene is essential for basal expression and can confer tissue-specific regulation to heterologous promoter constructs (35,40,41). The nuclear proteins SRF and YY1 bind to many CArG elements in vitro and function as positive and negative transcription factors, respectively (13).…”
Section: Discussionmentioning
confidence: 99%